Response of respiratory, gastrointestinal, and urinary tracts of buffalo calves following exposure to Pasteurella multocida B:2 - Salleh, Annas (2015)
Haemorrhagic septicaemia (HS) is an acute, fatal, septicaemic disease of ruminants, particularly in buffalo. HS is caused by a Gram-negative bacterium, Pasteurella multocida of specific serotypes; B:2 (Asian serotype) or E:2 (African serotype). Infection results in outbreaks and death of animals, which in turn leads to economic losses to the farmers. Animals surviving the outbreaks usually gain immunity and become lifelong carriers. These carrier animals are believed to shed P. multocida B:2 via the respiratory tract, transmitting the organism to the surrounding naive animals, resulting in yet another outbreak and formation of new carrier animals. It has been long proven that the respiratory tract plays an important role in the transmission of HS among animals. However, since HS is a septicaemic disease, the aetiological agent could be isolated from all organs at necropsy and recent study revealed a new theory of the involvement of gastrointestinal and urinary tracts in development or transmission of HS. Therefore, this study was conducted to determine the involvement of gastrointestinal and urinary tracts in development of acute HS as well as its transmission especially among carrier animals. Six buffalo calves were selected and divided into two groups. Group 1 was inoculated subcutaneously with 0.02 ml/kg of 1x109 cfu/ml of P.multocida B:2, while Group 2 was subcutaneously inoculated with 0.02 ml/kg of sterile phosphate buffer saline (PBS) and served as the negative control group. The buffalo calves were observed for clinical signs of HS. All buffalo calves of Group 1 were euthanised due to advanced clinical signs, while all buffalo calves of Group 2 survived and were euthanised at 72 h p.i.. At necropsy, the organs of the respiratory, gastrointestinal, and urinary tracts were collected and subjected to P. multocida B:2 isolation and concentration determination, as well as immunoperoxidase. The present study observed that the distribution of P. multocida B:2 based on the bacterial concentration and immunoperoxidase staining differs between the respiratory, gastrointestinal, and urinary tracts. In general, the distribution of P. multocida B:2 was observed to be significantly (p<0.05) high in the respiratory organs. However, the distribution and concentration of P. multocida B:2 in the gastrointestinal and urinary tracts, particularly in the liver, the small intestinal segments, and the kidneys were observed to be high. Severity of the pathological changes in these tracts was also compared. As expected, the lesions were most severe among the organs of the respiratory tract following gross, histopathological, and ultrastructural evaluations. The involvement of respiratory, gastrointestinal, and urinary tracts in transmission of HS from carriers was determined in this study. 12 buffalo calves were selected and equally divided into three groups; Group 1 served as acute infection group, Group 2 as commingling group, and Group 3 as negative control group. Buffalo calves of Group 1 were inoculated subcutaneously with 0.02 ml/kg of 1x105 cfu/ml of P. multocida B:2. Buffalo calves of Group 2 were not inoculated, but were allowed to commingle with buffalo calves of Group 1. Buffalo calves of Group 3 were inoculated subcutaneously with 0.02 ml/kg of sterile PBS. All buffalo calves were observed for clinical signs of HS, and all buffalo calves of Group 1 were euthanised at 24 to 48 h p.i., and transmitted the disease to the buffalo calves of Group 2, resulting in 3 buffalo calves to become carriers, while another had to be euthanised due to acute HS. The carrier animals of Group 2 and the negative control buffalo calves of Group 3 were subsequently subjected to three cycles of stress and immunosuppression by intramuscular injection of dexamethasone. At the end of the three cycles of immunosuppression, the carrier buffalo calves of Group 2, and the negative control buffalo calves of Group 3 were euthanised. At necropsy, samples of the respiratory, gastrointestinal, and urinary tracts were collected, and subjected to isolation and identification of P. multocida B:2, detection of P. multocida B:2 DNA by polymerase chain reaction (PCR), and immunoperoxidase for localisation of P.multocida B:2. Under the first cycle of immunosuppression, the carrier animals were observed to shed P. multocida B:2 via the respiratory, gastrointestinal, and urinary tracts following isolations of the organism from the nasal, rectal, and vaginal swabs. The immunoperoxidase technique was used to aid in localisation of P. multocida B:2 in respiratory, gastrointestinal, and urinary tracts of carrier animals. Pasteurella multocida B:2 was observed to localised in various organs of the respiratory, gastrointestinal, and urinary tracts. On the other hand, P. multocida B:2 DNA was detected in the tonsil, lungs, reticulum, ileum, and ureter of the carrier animals of Group 2. Nine buffalo calves and nine cattle calves were selected to compare the susceptibility between buffalo and cattle calves upon exposure to P.multocida B:2. The animals were divided into six groups. Group 1 and Group 2 consist of three buffalo calves, and three cattle calves, respectively. These groups were inoculated subcutaneously with 0.02 ml/kg of sterile PBS and served as the negative control groups. Group 3 and Group 4 consisted of three buffalo calves, and three cattle calves,respectively. These groups were inoculated subcutaneously with 0.02 ml/kg of 1x105 cfu/ml of P. multocida B:2. Group 5 and Group 6 consisted of three buffalo calves, and three cattle calves, respectively. These groups were inoculated intranasally with 0.02 ml/kg of 1x105 cfu/ml of P. multocida B:2. Subsequently, samples of observation and recording of clinical signs severity, whole blood for quantitation of bacteraemia, and blood plasma for quantitation of endotoxaemia were collected. Animals with advanced clinical signs were euthanised. It was found that all buffalo and cattle calves of Group 3 and 4 and 2 buffalo calves of Group 5 had to be euthanised due to severe clinical signs of HS, pathological changes, and septicaemia. On the other hand, all cattle calves of Group 6 survived,and were euthanised at 72 h p.i.. Blood endotoxin and P. multocida B:2 concentrations throughout the experiment revealed that endotoxaemia preceeded bacteraemia prior to the development of septicaemia. Thus, it was postulated that the respiratory immunophysiology of cattle might contribute to its resistance to HS. Based on high concentration of P. multocida B:2 in the lungs, liver,duodenum, jejunum, ileum, and kidney; high severity in scores in the lungs, abomasum, duodenum, jejunum, ileum, and kidney; isolation of P.multocida B:2 from the nasal, rectal and vaginal swabs of carrier animals;immunoreaction and P. multocida B:2 DNA detection from various organs of the respiratory, gastrointestinal, and urinary tracts of carrier animals; it was concluded that the respiratory, gastrointestinal, and urinary tracts play roles in the development and transmission of HS, although the respiratory tract remained as the most important system in HS transmission and development.